Diversity of the hepatitis C virus NS5B gene during HIV co-infection - Ngwaga, Tshegofatso (PLoS One, 2020)
Viral diversity is an important feature of hepatitis C virus (HCV) infection and an important predictor of disease progression and treatment response. HIV/HCV co-infection is associated with enhanced HCV replication, increased fibrosis, and the development of liver disease. HIV also increases quasispecies diversity of HCV structural genes, although limited data are available regarding the impact of HIV on non-structural genes of HCV, particularly in the absence of direct-acting therapies. The genetic diversity and presence of drug resistance mutations within the RNA-dependent RNA polymerase (NS5B) gene were examined in 3 groups of women with HCV genotype 1a infection, including those with HCV mono-infection, antiretroviral (ART)-naïve women with HIV/HCV co-infection and CD4 cell count <350 cells/mm(3), and ART-naïve women with HIV/HCV co-infection and CD4 cell count ≥350 cells/mm(3). None had ever been treated for HCV infection. There was evidence of significant diversity across the entire NS5B gene in all women. There were several nucleotides and amino acids with distinct distributions across the three study groups, although no obvious clustering of NS5B sequences was observed based on HIV co-infection or CD4 cell count. Polymorphisms at amino acid positions associated with resistance to dasabuvir and sofosbuvir were limited, although the Q309R variant associated with ribavirin resistance was present in 12 individuals with HCV mono-infection, 8 HIV/HCV co-infected individuals with CD4 <350 cells/mm(3), and 12 HIV/HCV co-infected individuals with CD4 ≥350 cells/mm(3). Previously reported fitness altering mutations were rare. CD8(+) T cell responses against the human leukocyte antigen (HLA) B57-restricted epitopes NS5B(2629-2637) and NS5B(2936-2944) are critical for HCV control and were completely conserved in 44 (51.8%) and 70 (82.4%) study participants. These data demonstrate extensive variation across the NS5B gene. Genotypic variation may have a profound impact on HCV replication and pathogenesis and deserves careful evaluation.